2017
DOI: 10.3892/ol.2017.6980
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‑3‑gallate induces apoptosis in acute promyelocytic leukemia cells via a SHP‑1‑p38α MAPK‑Bax cascade

Abstract: Abstract. Acute promyelocytic leukemia (APL) is characterized by a specific chromosomal translation, resulting in a fusion gene that affects the differentiation, proliferation and apoptosis of APL cells. Epigallocatechin-3-gallate (EGCG), a catechin, exhibits numerous biological functions, including antitumor activities. Previous studies have reported that EGCG induces apoptosis in NB4 cells. However, the molecular mechanism underlying EGCG-induced apoptosis remains unclear. The present study aimed to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Moreover, another study demonstrated that epigallocatechin-3-gallate treatment meaningfully inhibited the viability of leukemia cells in a dose-dependent way. Besides, Epigallocatechin-3-gallate treatment induced apoptosis and increased the levels of Bax protein expression [ 111 ]. Study results reported that green tea compound targets PML/RARα oncoprotein in the degradation and potentiates differentiation of leukemia cells in combination with ATRA via PTEN [ 112 ].…”
Section: Role Of Egcg In Inhibition and Prevention Of Various Typementioning
confidence: 99%
“…Moreover, another study demonstrated that epigallocatechin-3-gallate treatment meaningfully inhibited the viability of leukemia cells in a dose-dependent way. Besides, Epigallocatechin-3-gallate treatment induced apoptosis and increased the levels of Bax protein expression [ 111 ]. Study results reported that green tea compound targets PML/RARα oncoprotein in the degradation and potentiates differentiation of leukemia cells in combination with ATRA via PTEN [ 112 ].…”
Section: Role Of Egcg In Inhibition and Prevention Of Various Typementioning
confidence: 99%
“…These enzymes are serine-threonine protein kinases that regulate various cellular activities including proliferation, differentiation, apoptosis or survival, inflammation, and innate immunity (29). EGCG treatment was able to induce NB4 cell apoptosis by increasing phosphorylated (p)-p38α MAPK expression (30). In addition, other studies have found that EGCG also regulates ERK and JNK signaling pathways (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al indicated that polyphenols exerted anti-tumor actions as small molecular inhibitors of signaling cascades and src family kinase (38). EGCG induced apoptosis in human acute promyelocytic leukemia NB4 cells and increased the level of Bcl-2-associated X protein (Bax) protein expression via upregulating Src homology 1 domaincontaining protein tyrosine phosphatase (SHP-1)-p38αMAPK-Bax cascade (10). EGCG in combination with Am80 (a synthetic retinoid) synergistically induced apoptosis in human lung cancer cell line PC-9 and up-regulated expressions of growth arrest and DNA damage-inducible gene 153 (GADD153), death receptor 5, p21waf1 genes by increasing acetylation levels in nonhistone proteins such as p53, α-tubulin via down-regulation of histone deacetylase 4, 5, 6 (39).…”
Section: Dietary Polyphenols and Cancersmentioning
confidence: 99%
“…2018; 12 (6): 526-536. cardioprotective actions and anti-platelet properties, etc. (9,10). However, the structure-activity relationship of dietary polyphenols is still unclear.…”
Section: Introductionmentioning
confidence: 99%